(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the significance of the anthropocentric approach in linguistics and translation theory. The research emphasizes the central role of the human factor cognitive, emotional, and cultural experience in language understanding and translation processes. The anthropocentric perspective views language as a product of human cognition and treats translation as a complex activity that ensures semantic and pragmatic equivalence in intercultural communication. The study demonstrates the practical relevance of this approach in translation through theoretical arguments and illustrative examples.